God's δικαιοσύνη and Jesus' 'Hour' in John's Gospel: Divine Love in Action - Creevey, Paul Joseph (Biblica, 2023)
John’s Gospel uses the Greek noun δικαιοσύνη only twice (John 16,8.10) and the adjective δίκαιος three times (John 5,30; 7,24; 17,25). This study examines the context of these five uses in order to explore the meaning of δίκαιος/δικαιοσύνη in the Johannine Gospel. The central hypothesis is that the use of these terms in John is inextricably linked to the completion of Jesus’ 'hour' as God’s judgment on Jesus’ faithfulness to God’s will. The essay proceeds in three stages. First, it looks at how John uses δίκαιος/δικαιοσύνη in speaking of judgment as an example of God’s justice. Second, it argues that God’s δικαιοσύνη is reflected in John through Jesus’ commitment to the will of his Father to fulfill his 'hour'. Finally, it shows that through the completion of Jesus’ 'hour', in the sequence of events of his passion, death, and burial, as well as the empty tomb and appearance narratives, the Evangelist John, through Jesus’ life and mission, reveals a God who acts with δικαιοσύνη.